2000
DOI: 10.1021/ja993745h
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of Co2+ Ions in the Interior of Poly(propylene amine) Dendrimers Containing Fluorescent Dansyl Units in the Periphery

Abstract: We have investigated the interaction of Co 2+ ions (as nitrate salt) with dendrimers of the poly-(propylene amine) family functionalized in the periphery with fluorescent dansyl units. Each dendrimer nD, where the generation number n goes from 1 to 5, comprises 2 (n+1) dansyl functions in the periphery and 2 (n+1) -2 tertiary amine units in the interior. For comparison purposes, the behavior of a monodansyl reference compound (I) has also been investigated. The results obtained have shown that: (i) the absorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(76 citation statements)
references
References 69 publications
5
70
0
1
Order By: Relevance
“…There is no universal label and the choice of the reagent should be customized to the synthetic chemistry used. When NH 2 groups are involved one may use the Sanger reagent 51,52 or Dansyl [54][55][56] . The Sanger reagent is less prone to aggregation and its smaller size is advantageous at high g. (iv) The labelling method can quantify all free ends for 1rgtg max , that is,…”
Section: Discussionmentioning
confidence: 99%
“…There is no universal label and the choice of the reagent should be customized to the synthetic chemistry used. When NH 2 groups are involved one may use the Sanger reagent 51,52 or Dansyl [54][55][56] . The Sanger reagent is less prone to aggregation and its smaller size is advantageous at high g. (iv) The labelling method can quantify all free ends for 1rgtg max , that is,…”
Section: Discussionmentioning
confidence: 99%
“…In the field of chemical sensing, it has been demonstrated that luminescent dendrimers could be used for chiral amino alcohols, [96][97][98] and metal ion sensing. 95,[99][100][101] 3.1.1 Molecular imprinted polymers. A special case of fluorescent polymers are fluorescent molecular imprinted polymers.…”
Section: Fluorescent Polymersmentioning
confidence: 99%
“…They estimated that a single metal ion produced the quenching of 44 dye molecules. 63,99,234 Tonellato and co-workers modified silica nanoparticles via the reaction of commercially available silica nanoparticles with average size of 18 nm with a trimethoxysilane derivatized dansylamide as reporter and a picolinamide as Cu 2+ binding subunit. 77 In this case receptor and fluorophores are not bound together but the spatial proximity is ensured by selfassembly of the sensing elements.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…In all cases, the mechanism of switching off the fluorescence signal could be interpreted in terms of energy or intermolecular photo-induced electron transfer between transition metal ions and the excited state of the dansyl molecule from copolymers. [37] On the other hand, the selectivity studies have clearly demonstrated the higher selectivity of such photopolymers toward Fe 2+ ions in comparison with the others foreign ions under identical conditions. These results suggest that dansyl moiety in the side chain of the above copolymers could act as the special recognition site of a fluorescent chemosensor utilized for sensitive and selective detection of transition metal ions.…”
Section: × 10mentioning
confidence: 96%